Association between Cancer and Environmental Exposure to Glyphosate - Avila Vazquez, Medardo (2017)
Background: Argentina, Brazil, Paraguay and Uruguay farm transgenic seeds glyphosate resistant. Argentina annually utilizes 240,000 tonnes of glyphosate in agriculture. A change in the profile of morbidity and mortality is perceived in agricultural areas; cancer seems to prevail. Monte Maíz is a typical argentine agricultural town with 8000 inhabitants; the Mayor and residents of Monte Maiz requested an environmental health study due to perceived increase in cancer frequencies. Methods: An exploratory ecological study was developed to assess the urban environmental contamination and the frequencies and distribution of cancer through an environmental analysis of pollution sources including measurements of pesticides in water, soil and grain dust, and a cross-sectional study of cancer patients that explore associations with different variables. Results: Glyphosate was detected in soil and grain dust and was found to be at an even higher concentration in the village soil than in the rural area. 650 tonnes are used annually in the region and manipulated inner town. We do not find other relevant sources of pollution. Cancer incidence, prevalence, and mortality are between two and three times higher than the reference values (Globocan 2012, WHO) for the entire nation (706/100,000 persons vs. 217/100,000; 2123/100,000 persons vs. 883.82/100,000 and 383/100,000 persons vs. 115.13/100,000, respectively). Conclusion: This study detects high glyphosate pollution in association with increased frequencies of cancer in a typical argentine agricultural village, and by design, cannot make claims of causality. Other study designs are required, but if we corroborate the concrescence of high exposure to glyphosate and cancer.